A standardised computed tomography measurement method for distal fibular rotation - Vetter, Sven Y.; Uhlmann, Lorenz; Swartman, Benedict; Schnetzke, Marc; Keil, Holger; Franke, Jochen; Grützner, Paul Alfred; Beisemann, Nils (European journal of trauma and emergency surgery, 2021)
The aim of the study is to identify an ideal location to measure fibular rotation in the ankle joint using axial computed tomography (CT) scans. Another objective was to detect the average fibular rotation in the uninjured ankle joint in a large cohort.